Education to prevent ventilator-associated pneumonia in intensive care unit - Branco,Aline (2020)
ABSTRACT Objective: to evaluate nursing adherence to the Ventilator-Associated Pneumonia Prevention Bundle and the incidence rate, before and after Continuing education. Methods: a quasi-experimental, retrospective study with a total of 302 patients on mechanical ventilator admitted to the Intensive Care Unit. Data obtained from the application of the bundle, from June 2017 to June 2018. In December 2017, a training on the infection was carried out with 48 professionals. Results: the mean age of patients was 62.39±17.06 years old. Appropriate measures before and after training, respectively: position of the ventilator filter 94.8% and 96.2%, p=0.074; elevated headboard 88.4% and 94.5%, p<0.001; oral hygiene with chlorhexidine 89.5% and 98.2%, p<0.001; teeth brushing 80.8% and 96.4%, p<0.001; and cuff pressure 92.7% and 95.6%, p=0.002. Incidence density was 7.99 for 4.28 infections/1000 ventilators per day. Conclusion: the bundle application and education made it possible to increase adherence and decrease infection.